Shakespeare's Culture of Violence - Cohen, D. author. aut Link
VIII, 152 p.
Keywords: In this book, Derek Cohen studies the relationship of Shakespearean drama to the Western culture of violence. He argues that violence is an inherent feature and form of patriarchy and that its production and control is one of the dominant motives of the political system. Shakespeare's plays supply examples of the way in which the patriarchy of his plays - and hence, perhaps, of modern Western culture - absorbs, naturalizes, and legitimizes violence in its attempts to maintain political control over its subjects.